Diversity And Characteristics of Bladder Stones in Green Iguanas (Iguana iguana): A Case Report - Hendarti, Gracia Angelina; Sofyan, Miayu Soneta; Sari, Dian Ayu Kartika; Plumeriastuti, Hani; Proboningrat, Annise; Dhamayanti, Yeni; Soeharsono, Soeharsono; Lukman, Epy Muhammad; Palupi, Tantri Dyah Widhi; Hernanda, Ary Setya; Ritonga, Mudhita Zikkrullah (Jurnal Medika Veterinaria, 2025)
Bladder stones represent a significant and increasingly common health issue in captive green iguanas (Iguana iguana), often resulting from improper husbandry practices. This case report examines the diversity and characteristics of bladder stones in five green iguanas (three females, two males) presenting with abdominal enlargement and decreased appetite. Surgical removal (cystotomy) was performed, followed by detailed morphometric and chemical analyses of the extracted stones. The stones varied in size (15.3655.01 g), shape, and color (white, cream, and dark brown), yet chemical composition was consistently dominated by calcium oxalate (5260%), tricalcium phosphate (2328%), and uric acid (1012%). Morphometric analysis showed low variation (50%) across measured parameters, indicating homogeneity among the samples. Notably, lighter iguanas tended to harbor heavier stones, suggesting a correlation with disease progression rather than sex or stone color. These findings reinforce the role of dietary imbalances, dehydration, and the anatomical peculiarities of the iguana urinary system in stone formation. Early detection, appropriate diet, and optimal hydration are critical to prevent urolithiasis. This report contributes to the limited data on iguana urolithiasis in Indonesia and highlights the need for broader studies to explore preventive strategies.